Effect of Formulation of Effective Microorganism (EM) on Post Treatment Persistence, Microbial Density and Soil Macronutrients - and Kirithiga, Karthick Raja Namasivayam* (Recent Research in Science and Technology, 2010)
Effective Microorganisms (EM), a culture of coexisting beneficial microorganism predominantly consisting of lactic acid bacteria, photosynthetic bacteria, yeast, fermenting fungi and actinomycetes that are claimed to enhance microbial turnover in soil and thus known increase soil macronutrients and increases plant growth and yield. In the present study, Pot trails were conducted to evaluate the effect of various formulations of Effective microorganisms (EM) viz rice washed water, rice bran and oil cake, sugar syrup, rice bran, oil cake and sugar on post treatment persistence of EM and soil nitrogen, phosphorous and potassium level. The experiment was initiated with four groups of five replications. Group one was the negative control with only water added throughout the study. Group two was the second control with respective formulating agents without EM (0.01%). Group three was only EM solution (0.01%) and group four was respective formulations of EM as granulated form (0.01%). Among the formulations rice bran +oil cake +sugar syrup formulation recorded maximum N,P,K level followed by sugar syrup. Moreover the occurrence of respective microbial member was recorded in all the formulations and maximum microbial count was recorded in rice bran, oil cake and sugar syrup formulation. Similarly the pots treated with EM with rice bran+oil cake+ sugar syrup increased the microbial density other than individual members of EM of the soil.